Coaching-Based Academic Supervision Management Using the Tirta Model to Improve Teachers' Pedagogical Competence - Erwin Kustamaji; Nana Herdiana Abdurrahman (Journal of Innovation and Research in Primary Education, 2026)
Teachers' pedagogical competence remains a critical challenge in Indonesian elementary education despite various professional development initiatives. Traditional evaluative supervision approaches have proven insufficient in fostering sustainable teacher development. This study examined the implementation of coaching-based academic supervision using the TIRTA (Goals, Identification, Action Plan, Responsibility, Appreciation) model to enhance teachers' pedagogical competence in elementary schools. A descriptive qualitative case study was conducted at SDN Pancawangi and SDN Sindangjaya in Cianjur Regency, West Java. Data were collected through in-depth interviews with principals and teachers, participatory observations of supervision sessions, and analysis of supervision documents. Data analysis followed Miles, Huberman, and Saldaña's interactive model, with trustworthiness established through triangulation and member checking. Findings revealed that TIRTA-based supervision was implemented systematically through collaborative planning (participatory needs assessment, SMART goals), structured five-stage implementation (reflective dialogue, co-constructed action plans, mutual accountability), comprehensive evaluation (82% target achievement, constructive feedback), and sustained follow-up (continuous monitoring, progressive competency development). The coaching approach transformed supervision relationships from evaluative to developmental, creating psychological safety and cultivating teachers' autonomous motivation and self-directed learning capacities. The TIRTA model effectively operationalizes adult learning theory, coaching principles, and self-determination theory, offering promising direction for sustainable teacher professional development in elementary education contexts.